P-143 INTRAOPERATIVE FLUORESCENCE ANGIOGRAPHY WITH INDOCYANINE GREEN (ICG) IN EMERGENCY LAPAROSCOPIC HERNIA REPAIR. (13th October 2022) - Bascuas, B; Licardie, E; Ramirez, A; Guadalajara, J
Abstract: Aim: Bowel incarceration is common complication in incarcerated hernias, which involves one of the most frequent emergent surgical pathologies. Real-time fluorescence angiography with ICG is a reliable technique that allows surgeons to assess intestinal blood flow. However, this technique is rarely used in emergency surgery such as incarcerated hernia repair. Materials & methods: We present the case of a 64-year-old patient with medical history of high blood pressure, atrial fibrillation and hepatitis C, complaining of abdominal pain and vomiting associated to painful inguinal hernia in the past 12 hours. The patient presented inguinal incarcerated hernia without any signs of external complication or elevation of infection and inflammatory parameters in blood test. Results: We decided to carry out an urgent hernia repair performing transabdominal preperitoneal (TAPP) approach. Once the hernia was repaired, intraoperative ICG fluorescence angiography was performed in order to evaluate intestinal viability. ICG fluorescence revealed the presence of irreversible ileal ischemia (12 cm) needing resection. Through mini-Pfannenstiel incision we performed the resection and a side to side stapled anastomosis. Postoperative course was uneventful and the patient was discharged 3 days after the surgery. Conclusions: The combination of laparoscopic approach and ICG fluorescence angiography seems to be an actual useful solution, combining the advantages of minimally invasive surgery and avoiding the risk of bowel perforation due to unnoticed ischemia thanks to the assess of intestinal perfusion.